2016
DOI: 10.1186/s13018-016-0443-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of suramin on inhibiting fibroblast proliferation and preventing epidural fibrosis after laminectomy in rats

Abstract: BackgroundEpidural fibrosis often causes serious complications in patients after lumbar laminectomy and discectomy and is associated with the proliferation of fibroblasts. Suramin is known to have an obvious inhibitory effect on the coactions of many growth factors and their receptors, but little was previously known about the effect of suramin on fibroblast proliferation and the progress of epidural fibrosis.MethodsWe illustrated the effect of suramin on cultured fibroblasts of rats with different concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Fibrosis of the local dura mater following laminectomy, which is not uncommon, leads to worse patient outcomes ( 42 , 43 ). The current treatment options, namely, conservative treatment and scar excision, are unsatisfactory ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis of the local dura mater following laminectomy, which is not uncommon, leads to worse patient outcomes ( 42 , 43 ). The current treatment options, namely, conservative treatment and scar excision, are unsatisfactory ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated the epidural fibrosis on dura mater after laminectomy operation, which ultimately results in a negative outcome for patients (8,29). Various studies have attempted to solve this problem by local drug applications (30,31) and biomaterials (32).…”
Section: Discussionmentioning
confidence: 99%
“…additionally, further studies have illustrated that the excessive proliferation of fibroblasts in the operative region is the most significant element of local fibrosis formation (4,5). Therefore, the methods of inhibiting fibroblast proliferation to reduce fibrosis have become an attractive area of study and previous studies have demonstrated positive results (6)(7)(8). However, there are numerous limitations for clinical application, hence further research is still required to solve the problem completely.…”
Section: Introductionmentioning
confidence: 99%
“…Paraspinal muscle dissection and bone removal lead to fibroblast migration from periosteum and muscle tissue to the site of laminectomy. Hematoma resulting from surgical manipulation also transforms into granulation tissue, which is in turn converted into epidural scar tissue 22, 24, 25. Songer et al suggested that epidural fat tissue extends from the posterior epidural compartment to the intervertebral foramen, and that with its semi-viscous nature it replaces epidural fibrosis tissue, which compresses the dural sac and nerve roots 26 …”
Section: Discussionmentioning
confidence: 99%